3h=-2h-10

Simple and best practice solution for 3h=-2h-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3h=-2h-10 equation:


Simplifying
3h = -2h + -10

Reorder the terms:
3h = -10 + -2h

Solving
3h = -10 + -2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '2h' to each side of the equation.
3h + 2h = -10 + -2h + 2h

Combine like terms: 3h + 2h = 5h
5h = -10 + -2h + 2h

Combine like terms: -2h + 2h = 0
5h = -10 + 0
5h = -10

Divide each side by '5'.
h = -2

Simplifying
h = -2

See similar equations:

| 16x+-15+-1=-15 | | 12x+180=-720 | | x^2+82x+81=0 | | 5logx^3=20 | | -5y+6-y=-5y-4 | | 3+9c=10c | | 4x+30=x-15 | | 3+6f=5f | | x^2+81x+81=0 | | 5b-10=10b | | -7j+10=-10-9j | | 2x+6x=-85+5 | | 2g=-16 | | -g=10g | | -10+6u=4u | | n+19=3 | | -1-3x=9x-13 | | -w+3-10w=4-10w | | -6q=-4q-10 | | 4X^1=50 | | -5s=-8s+9 | | .4x-y+6=0 | | 3n-8/2*6=6 | | 4m-8=3m | | 6+10z=-10+6z | | 4z=6z+8 | | 2j=j+9 | | X^2-6x-96=-130 | | -3f+10=-10+7f | | -3f+10=-10 | | -5b-6=-111 | | 7m=8+6m |

Equations solver categories